Upaya Peningkatan Manajemen Pelayanan Kesehatan Di Rumah Sakit: Tinjauan Teoritis - Astria Apriliavini Priscila Palenewen; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
The hospital as a health service institution that organizes individual health services in a complete manner that provides inpatient, outpatient and emergency services. Efforts to improve health services as an agreement on setting long-term goals and visions which then become a common reference in achieving the goals that have been set. The purpose of this theoretical review is to find out how to improve health services in hospitals. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are by increasing efforts such as providing adequate infrastructure facilities including from a physical perspective, besides being efficient, fair, timely, secure, integrated, focused, reliable and effective. It can be concluded that efforts to improve the quality of health services as a process of meeting the needs and life expectancy of patients, both internally and externally. Quality can also be associated as a gradual and continuous improvement process. In general, the quality of health services focuses on the concept that health services have three main foundations, namely quality, access and cost.